2024
DOI: 10.1111/jgs.18705
|View full text |Cite
|
Sign up to set email alerts
|

Is the Montreal cognitive assessment culturally valid in a diverse geriatric primary care setting? Lessons from the Bronx

Marnina B. Stimmel,
Ariela R. Orkaby,
Emmeline Ayers
et al.

Abstract: BackgroundEfficacy and validity of the MoCA for cognitive screening in ethnoculturally and linguistically diverse settings is unclear. We sought to examine the utility and discriminative validity of the Spanish and English MoCA versions to identify cognitive impairment among diverse community‐dwelling older adults.MethodsParticipants aged ≥65 with cognitive concerns attending outpatient primary care in Bronx, NY, were recruited. MoCA and neuropsychological measures were administered in Spanish or English, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…A total of 1,042 participants (86.8%) completed 12 months of follow-up. There were no statistically significant group differences that the Montreal Cognitive Assessment (MoCA) test cutoff points for detecting dementia that were established in mostly white populations were too high in our US-based study sample that consisted of mostly Black or Hispanic people 16 . Black and Hispanic participants in the US-based Health and Retirement study were reported to have missed or delayed diagnosis of dementia more often compared to white people 17 .…”
Section: Secondary Outcomementioning
confidence: 66%
See 2 more Smart Citations
“…A total of 1,042 participants (86.8%) completed 12 months of follow-up. There were no statistically significant group differences that the Montreal Cognitive Assessment (MoCA) test cutoff points for detecting dementia that were established in mostly white populations were too high in our US-based study sample that consisted of mostly Black or Hispanic people 16 . Black and Hispanic participants in the US-based Health and Retirement study were reported to have missed or delayed diagnosis of dementia more often compared to white people 17 .…”
Section: Secondary Outcomementioning
confidence: 66%
“…Given that we enrolled only adults with cognitive concerns, the 5-Cog sensitivity and specificity is reasonable. In comparison, in the 5-Cog subsample that agreed to additional testing, we reported that the MoCA test (<17) had a sensitivity of 65% for English and 64% for Spanish versions, and specificity of 77% for English and 73% for Spanish versus the neuropsychologist's independent diagnosis of cognitive impairment 2,16 . Unlike cognitive assessments with higher stated sensitivity and specificity that were validated in samples with cognitively healthy controls 5,9,13 , test-negative cases in the 5-Cog arm were not cognitively normal as they had cognitive concerns 36 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation